THE CATEGORY VERB IN DIFFERENT LANGUAGES AND ITS GRAMMATICAL FEATURES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the grammatical features of verbs in English and Uzbek.